Chemical modification of polymers: current and future routes for synthesizing new polymeric compounds - Wan Yunus, Wan Md. Zin (2002)
Chemical modification of polymers is one of the methods used to synthesize new polymeric compounds. It is the most active fields of research in polymer sciences for the past 30 years and enables us to introduce functional or reactive groups into polymers, to alter polymer surfaces, to provide side chain substituents, etc,. Important products of polymer modification include polymeric reagents, functionalised resins, catalyst and media for trapping reaction interdiates organometallic polymers acid carrier for active molecules. This lecture give an overview of our work on preparation and application of poly (hydroxamic acid) resins, lipase modification and immobilization for hydrolysis of palm oil and fatty ester syntheses, and graft copolymerization of sago starch.